Statistically significant chuckles: who is using humour at scientific conferences? - Mammola, Stefano; Fontaneto, Diego; Santangeli, Andrea; Oswald, Krista Natasha; Correia, Ricardo; Meierhofer, Melissa B.; De Santis, Vanessa; Stout, Victoria (Royal Society Publishing, 2026)
We’ve all been there: 11.47, swamped by a long stretch of dense scientific talks at a conference. Six slides into a hyper-technical presentation, the speaker suddenly cracks a joke. The room erupts. Shoulders relax. Minds re-engage. Humour is a powerful but underused tool in scientific communication, often sidelined by academic norms that view levity as unprofessional. Social biases can further shape who feels safe joking without risking credibility. At 14 biology-related conferences, we collected data on humour use across 531 talks. Jokes clustered at the beginnings and ends of talks, with an extra bump in successful jokes midway through. Most jokes (66%) earned only polite chuckles. Humour success was unrelated to the type of joke or form of delivery; however, male speakers told about 0.35 more jokes per talk, and both male and native speakers had a 10% higher probability of eliciting laughter. This suggests how social dynamics influence who feels comfortable using humour and whose jokes resonate with the audience. Until academia reckons with these biases, humour will remain a privilege. Still, for those brave enough or granted the social licence, a well-placed zinger can turn a forgettable talk into one people actually remember—and perhaps even enjoy.